PEMBERDAYAAN IBU HAMIL RESIKO TINGGI MELALUI PROGRAM JAMINAN PERSALINAN DI PUSKESMAS TEMBOKREJO KECAMATAN GUMUKMAS KABUPATEN JEMBER - Riza Umami (Politeknik Kesehatan Kemenkes malang, 2018)
The health status of a country is influenced by the existence of health facilities that can carry out health care efforts such as the allocation of funds for delivery through the Jampersal program. The purpose are to improve the understanding of high risk pregnant women through the Jampersal program. The results showed that pregnant women were able to carry out pregnancy screening at risk and were able to fulfill the Jampersal program.